Altered splenic [(89)Zr]Zr-rituximab uptake in patients with interstitial lung disease not responding to rituximab: could this indicate a splenic immune-mediated mechanism? - Adams, Human (Am J Nucl Med Mol Imaging, 2020)
Rituximab (RTX) for immune-mediated inflammatory disease (IMID) with interstitial pneumonitis (IP) results in non-response in about a third of patients for reasons not well understood. Complete peripheral B-cell depletion in IMID-IP does not seem to correlate with successful treatment outcome. A hypothesis is that splenic B cells might play a role in B-cell recovery and attraction of naïve B cells in non-responsive patients. The aim of this post hoc analysis of clinical trial data is to search for indicators in [(89)Zr]Zr-rituximab PET/CT data from the spleen that might explain non-responsiveness. PET/CT data of 20 patients with IMID-IP, who were enrolled in a phase II trial and treated with RTX were analyzed. Clinical outcome was categorized into responders (RSP) and non-responders (NR) after 6 months of initial RTX by two independent pulmonologists. Patients were examined separately to search for associations between clinical outcome, splenic activity on PET/CT, lymphocyte counts and other biomarkers. Treatment failure was found in 6/20 patients (30%) while all patients exhibited B-cell depletion from the circulation. NR patients demonstrated significantly higher splenic activity than RSP patients (non-preload protocol: SUV 4.9±1.96 and SUV 2.3±1.08 respectively, P=0.025). No correlations between treatment outcome and serum lymphocyte subsets were found. Our findings suggest a potential splenic mechanism in IMID-IP patients non-responding to RTX and warrant further consideration and investigation.